Semantic Classification of Basar Verses In Meccan Chapters: A Comparative Study Between Al-Razi And Ibn ‘Ashur - Nur Farhana Binti Baharuddin (Universiti Sains Islam Malaysia, 2025)
Matric: 3150284 (FPQS)